Seismic Behavior Analysis of Damaged Steel Fiber-Reinforced High-Strength Concrete Frame Joints Strengthened by FRP - Wang Tingyan; Zhou Yun; Zhang Junwei (Advances in Civil Engineering)
In this paper, the seismic behavior of fiber-reinforced polymer (FRP) strengthened and unstrengthened steel fiber-reinforced high-strength concrete frame joints under low cyclic loading was tested. Then, the nonlinear finite element program was used to simulate the seismic behavior of FRP strengthened and unstrengthened steel fiber-reinforced high-strength concrete frame joints under low cyclic repeated load. The influence of FRP bond direction on the seismic behavior of steel fiber-reinforced high-strength concrete frame joints was studied. Through the comparison of the test values and numerical simulation values of the hysteretic curve, skeleton curve, energy dissipation capacity, displacement ductility, bearing capacity degradation, stiffness degradation, and other performance indexes of frame joints, the rule was obtained. The results showed that the 45° bonding direction of carbon fiber cloth is better than the 0° bonding direction, and the digital simulation results are in good agreement with the test results. Therefore, the constitutive model, element, end constraint, and loading method used in the finite element numerical simulation of this paper were reasonable, which can provide reference for the similar research in the future.